Vildagliptin-induced acute pancreatitis without enzyme elevation - Mungan, Zeynel; Attila, Tan; Ünal Kabaoğlu, Zeynep; Vural, Metin (Turkish Journal of Gastroenterology, 2017)
Abstract We describe 2 patients with diabetes mellitus, presenting with upper abdominal pain. Although imaging findings were consistent with acute pancreatitis (AP), serum amylase and lipase levels were within normal limits. In both the cases, the only identifiable diagnostic culprit was vildagliptin. This is the first reported case of vildagliptin causing AP clinically and radiographically without elevated serum pancreatic enzymes. In conclusion, even when serum amylase and lipase levels are normal, AP should be kept in mind when making a differential diagnosis of patients with diabetes mellitus who present with abdominal pain and take dipeptidyl peptidase-4 (DPP-4) inhibitors. Cite this article as: Mungan Z, Attila T, Kabaoğlu ZÜ, Vural M. Vildagliptin-induced acute pancreatitis without enzyme elevation. Turk J Gastroenterol 2017. 2017; 28: 514-7.